1973
DOI: 10.1063/1.1654761
|View full text |Cite
|
Sign up to set email alerts
|

Laser mirror damage in germanium at 10.6 μm

Abstract: Damage in the germanium output mirror of a TEA CO2 laser shows a periodicity of 10.6 μm, the laser wavelength. A mechanism is proposed in which scattered and cavity radiation interfere. An interference mechanism is confirmed by experiments outside of the laser cavity. Periodic damage is obtained in thin films irradiated at angles other than the normal where the fringe spacing is modified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
174
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(201 citation statements)
references
References 4 publications
4
174
0
3
Order By: Relevance
“…This fundamental idea has been first suggested by Emmony et al 5 and was later improved by several other authors. 4,6 Particularly, the work of Sipe et al 4 represents a first-principle theory which takes into consideration the interaction of an electromagnetic wave with a microscopically rough surface, which includes also the possible excitation of surface polaritons.…”
Section: Comparison With the Conventional Theory On Lipssmentioning
confidence: 80%
See 1 more Smart Citation
“…This fundamental idea has been first suggested by Emmony et al 5 and was later improved by several other authors. 4,6 Particularly, the work of Sipe et al 4 represents a first-principle theory which takes into consideration the interaction of an electromagnetic wave with a microscopically rough surface, which includes also the possible excitation of surface polaritons.…”
Section: Comparison With the Conventional Theory On Lipssmentioning
confidence: 80%
“…It is generally accepted that this type of wavelength ripple arises from optical interference effects due to the superposition of the incident radiation with a surfaceelectromagnetic wave which is created at the rough surface during the irradiation and which is scattered along the surface. 2,[4][5][6] With respect to the irradiation with femtosecond laser pulses, ripples with spatial periods close to the wavelength have been reported on various absorbing materials such as metals, 7 ceramics, 8,9 and semiconductors. [10][11][12][13] Interestingly, in most of these cases the ripple period is somewhat smaller than the wavelength and their orientation is mostly perpendicular to the electric-field vector.…”
Section: Introductionmentioning
confidence: 99%
“…Emmony et al suggested in 1973 that LSFLs were a consequence of interference between the incident laser beam and surface-scattered waves. 4 In 1983, Sipe et al established a first-principles theory for LSFL formation, overcoming the physically inconsistent "surfacescattered wave" concept, by modeling the effect of surface roughness on the electromagnetic field. 21 The theory of Sipe et al, also referred to as the efficacy factor theory, or η theory, in this article, was commonly accepted for the formation of LSFLs.…”
Section: Introductionmentioning
confidence: 99%
“…1 The most common LIPSSs, also referred to as ripples, consist of wavy surfaces which can be produced on metals, 2,3 semiconductors, 4,5 and dielectrics. 6 When created with a linearly polarized laser radiation at normal incidence, these ripples have a periodicity close to the laser wavelength and a direction orthogonal to its polarization.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, the two most practical structures are introduced. It is well known that parallel ripple structures are formed on the surfaces of various types of materials with multiple pulse irradiation of a linearly polarized laser beam with nanosecond or longer pulses [24,25]. Such structures are called laser-induced periodic surface structure (LIPPS).…”
Section: Surface Micro-and Nanostructuringmentioning
confidence: 99%